Prediction of uterine myoma growth rate: what's new? (Literature review) - Gladchuk, I.; Salekh, O. (Journal of Education, Health and Sport, 2024)
Uterine fibroid remains a relevant issue in modern gynecology and reproductive medicine as the most common benign tumor of the female reproductive organs. Comprehensive diagnosis of the condition of the myomatous nodule and its potential growth rate plays a significant role in the rational selection of treatment tactics for women of reproductive age with uterine fibroids. Objective. To study and analyze existing methods of diagnosis and prediction the growth of uterine fibroids. Matherials and methods. Information search was conducted in the scientific literature in domestic and foreign publications, 46 sources were studied and analyzed. In the course of the study, a meta-analysis of the information obtained was carried out as to the set goal. Results and discussion. At present, at least three main mechanisms of activation of signal pathways stimulating leiomyocyte to pathological growth and division have been elucidated: cytokines, growth factors, and hormone-dependent channels. All links in the activation of signal pathways affecting the cell, which subsequently lead to pathological proliferation and tumor transformation, are interconnected. In recent years, the pathogenesis of uterine fibroids has been actively studied not only at the tissue level but also at the genetic and epigenetic levels. It has been definitively proven that disturbances in microRNAs, both tissue-specific and stable, play a leading role in regulating the expression of key genes associated with the pathogenesis of uterine leiomyomas, both in tumor foci and in biological fluids. Conclusions. Study of the expression of microRNAs is a promising method for understanding the further development of the pathological process and for predicting the growth of uterine fibroids.